Expeditious Microwave-Assisted Synthesis of Functionalized Oxaphosphaphenanthrenes and Chromenes via Multicomponent Reactions of Trivalent Phosphorus Nucleophiles - Hossaini, Zinatossadat; Rostami-Charati, Faramarz; Fereshteh Hayerizadeh, Seyedeh (Combinatorial Chemistry & High Throughput Screening, 2012)
Stable derivatives of oxaphosphaphenanthrenes were prepared by using the reactions of dialkyl acetylenedicarboxylate with 3-bromo-2-naphthol in the presence of trimethyl or triphenyl phosphite under microwave conditions at 70°C in good yields. Under similar conditions, chromene derivatives were produced by using triethyl phosphite and dialkyl acetylenedicarboxylate in the presence of OH-acids in excellent yields
Keywords: chromenes